Green Life Education Habit (GLEH) for Sustainability Lifestyles based Locally in Schools - Azis, Daska; Yusuf, Rusli; Hasan, Ishak; ., Husaini; ., Niswanto; ., Suhendro (Journal of Posthumanism, 2025)
The Merdeka Curriculum represents a transformation that responds to current global challenges. This complexity demands adaptive strategies that are locally relevant yet globally oriented. Green Life Education Habit (GLÉH) is a conceptual model designed to integrate these needs. GLÉH provides a framework for fostering sustainable lifestyle character through P5 (Pancasila Student Profile Strengthening Project) activities in schools. This research specifically aims to position GLÉH as a strategy to reinforce sustainable lifestyles. A mixed-method approach was employed, utilizing data collection techniques such as in-depth interviews, literature review, and document analysis. Influence tests and descriptive analysis were used to interpret the collected data. The findings indicate that GLÉH serves as a strategic innovation for promoting sustainable lifestyles in schools.